Employee Performance Assessment With Human Resources Scorecard And Ahp Method (Case Study : PT. PLN (Persero) North Sumatra Generation) - Lubis, Andrew Satria; Alfi Amalia (TALENTA Publisher, Universitas Sumatera Utara, 2021)
How does PT. PLN KITSBU measures the performance of human resources. PT. PLN KITSBU utilizes the Employee Performance Information System (SIMKP) application. By using the human resource scorecard and AHP (Analytic Hierarchy Process) method, you can get employee performance evaluations that have never been done in a company. The human resources scorecard method itself is a measurement system that connects human resources with strategy. Then, the AHP method is used to make employee performance decisions. The purpose of this study is to determine employee performance indicators and to find weights from all angles. And suggestions for companies, with which to improve in the future. The research results obtained 18 KPIs from 4 perspectives (including 4 KPIs from financial perspective, 3 KPIs for consumers or consumers, 7 KPIs for internal business composition and 4 KPIs for growth and learning). From a financial perspective, the weighted score is 3.341 (moderate), customers or consumers are 3.524 (good), the composition of the internal business is 3.357 (moderate), and growth and learning is 3.38 (moderate).